Evaluasi Program Pembinaan Latihan Pencak Silat di Sasana Djiwo Ketawang dengan Metode CIPP - Berlian Fernanda Putri; Heri Wahyudi; Himawan Wismanadi; Noortje Anita Kumaat (Lembaga Pengembangan Kinerja Dosen, 2025)
Research Problems The coaching process and training programs at Sasana Djiwo Ketawang have been implemented but have not yet reached maximum achievement. Research Objectives: This study aims to assess the effectiveness of martial art training program at Sasana Djiwo Ketawang using the CIPP model, including: (1) context evaluation, (2) input evaluation, (3) process evaluation and (4) product evaluation. Methods: The research method used is descriptive quantitative using a questionnaire and descriptive qualitative conducted by interview and observation and documentation as supporting data. Results: The results of this evaluation research show an overall average score of 2.89 in the good category, with a context evaluation score of 3.10 in the good category, an input evaluation score of 2.99 in the good category, a process evaluation score of 3.38 in the very good category and a product evaluation score of 2.09 in the poor category. The context aspect is considered successful, but the input aspect needs improvement, especially in athlete resources with the main obstacle being the lack of government funding in fostering achievement training. The process aspect is quite good, but the implementation of training has not been maximized even though coaching and monitoring evaluation have been running. This causes pencak silat achievements in Sasana Djiwo Ketawang not to be able to compete at the regional and national levels. Conclusion: For the overall results of the evaluation, Sasana Djiwo Ketawang has been running well, however, regular evaluations are still needed to improve coaching performance, try out scheduling for athletes' match flying hours and a more varied and efficient training program on target.